1992
DOI: 10.1007/bf00145019
|View full text |Cite
|
Sign up to set email alerts
|

The application of cultural and social capital: a study of the 25th year reunion entries of prep school and public school graduates of Yale College

Abstract: This article compares the post-college experiences of graduates of elite prep schools, non-elite prep schools and public schools who attended Yale College in the early 1960s. Drawing on previous research, and on Bourdieu's theory of social reproduction, it was hypothesized that Yale graduates who had attended public secondary schools would be more likely than Yale graduates who had attended prep schools to accumulate what Bourdieu calls 'cultural capital,' but that Yale graduates who had attended prep schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…For upwardly mobile women from working‐class backgrounds, college, while likely to be an experience in which unpreparedness and alienation were salient, also represented a necessary activity if their goal was in fact to “leave” the working class. Education is traditionally seen as a primary means of upward mobility; indeed, a liberal arts education in particular was seen as an expectation for membership in the upper middle class by the interviewees in Wentworth and Peterson's (2001) study (see also Zweigenhaft, 1992). One strategy, therefore, for assessing the ways in which women from working‐class backgrounds saw college as necessary in order for them to meet a particular goal is to examine whether or not they viewed college as an opportunity for social mobility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For upwardly mobile women from working‐class backgrounds, college, while likely to be an experience in which unpreparedness and alienation were salient, also represented a necessary activity if their goal was in fact to “leave” the working class. Education is traditionally seen as a primary means of upward mobility; indeed, a liberal arts education in particular was seen as an expectation for membership in the upper middle class by the interviewees in Wentworth and Peterson's (2001) study (see also Zweigenhaft, 1992). One strategy, therefore, for assessing the ways in which women from working‐class backgrounds saw college as necessary in order for them to meet a particular goal is to examine whether or not they viewed college as an opportunity for social mobility.…”
mentioning
confidence: 99%
“…In what ways does class background shape people's experiences at college? Are elite institutions of higher education navigated differently by people from different class backgrounds?Zweigenhaft (1992, 1993) documented the different strategies that men from public and private secondary schools used in their pursuit of social and cultural capital at elite colleges in the 1960s. Indeed, the very nature of their belonging to these institutions is predicted by their pre‐college, class‐based schooling: Men from public high schools are more likely to be in Phi Beta Kappa, for example, while those from private boarding schools are more likely to be in elite social clubs (Zweigenhaft, 1993).…”
mentioning
confidence: 99%
“…The argument here, however, is not merely that there is competition for the attendance of prep school graduates at reunions, or for their contributions, but that the prep schools play a larger part in their identities, and their colleges may play a smaller part than they would if they had attended public schools. As has been noted, previous research on Yale graduates revealed that public school graduates were more likely than prep school graduates to send in biographical material to appear in their 25-year reunion books (Zweigenhaft 1992), and these current studies of Wesleyan alumni show that public school graduates were more likely than prep school graduates to attend their reunions 30 to 45 years after graduation, and to contribute to the annual fund.…”
Section: Discussionmentioning
confidence: 76%
“…Drawing on reunion books published 25 years after they graduated from Harvard and Yale, Zweigenhaft (1992Zweigenhaft ( , 1993b also showed that the public school graduates were more likely to have gone on to obtain doctoral degrees, and the graduates of prep schools were more likely to have obtained M.B.A. degrees. The prep school graduates were more likely than the public school graduates to have reported membership in country clubs, city clubs, yacht clubs or polo clubs.…”
mentioning
confidence: 92%
“…Another way in which political contributions can give clients more bargaining power with auditors is by providing politically connected client executives with a form of social capital, which they can use as a bargaining tool. Social capital refers to the kinds of interpersonal connections that can enhance one's professional advancement (Zweigenhaft 1992). Aslan and Grinstein (2011) argue that political connectedness can be treated as one form of "social capital"…”
Section: Political Contributions Client Bargaining Power and Auditomentioning
confidence: 99%